Digitalization-Based Religious Tourism Village Development Strategy Case Study in Nyatnyono Village, Semarang Regency - Meirinaldi, Meirinaldi (Jurnal Indonesia Sosial Sains, 2023)
The digital village is a new strategy for urban development and management. Currently, villages rarely utilize online media for information exchange. When people need information, they have to visit the village office to request the necessary information and communicate with village members to convey it. The Digital Village program aims to provide internet access to villages that previously had no internet connectivity at all. Conceptually, a digital village is a program that transforms villages into development areas that empower communities with adequate information technology facilities. In the context of the government, the massive implementation of technology began with Presidential Instruction Number 3 of 2003 regarding the implementation of electronic government. With quality and competitive village development, the quality of information, systems, and services positively influences user satisfaction. User satisfaction and outcomes (organizational objectives) are among the main goals that the government must achieve in providing services to the community. The implementation of e-government in Village Governments can be a key intervention in driving villages towards progress. This research is descriptive research. The approach used is qualitative and conceptual. The data sources used are secondary data. Data analysis is conducted descriptively and qualitatively. Conclusions are drawn using deductive methods, which involve drawing conclusions from general to specific, particularly related to the research topic of Digitalization-Based Religious Tourism Development Strategies in the Village. This study found that Nyatnyono Tourism Village is a religious tourism village that offers pilgrimage tours of nature and traditional cultural heritage located in Semarang Regency. The tourism attractions in Nyatnyono Tourism Village include Wali Bathing Water, river tracking tours, salak fruit garden tours, arts and cultural tours, wali pilgrimage, and more. The accessibility to the tourism village is easy, and the tourism facilities in Nyatnyono Tourism Village are complete, including a mosque, musholla, security posts, public toilets, and even vintage bicycles. The management of Nyatnyono Tourism Village has shifted to using digital media to promote the village. With tourism digitalization, the management provides information about tourist attractions, tour packages, and supporting components through interactive websites and social media platforms to engage with tourists and provide information. In practice, digitalization in Nyatnyono Tourism Village through social media has been highly effective, as visitors can easily access information about the tourism village and directly book their accommodations online with available tour packages. Embracing the concept of "from the community, for the community," the management of digital tourism in Nyatnyono Tourism Village starts with the planning process by creating social media accounts and a website as promotional tools.